Extracellular Vesicles From Hyperammonemic Rats Induce Neuroinflammation in Cerebellum of Normal Rats: Role of Increased TNFα Content - Izquierdo-Altarejos, Paula; Martínez-García, Mar; Felipo, Vicente (Frontiers in Immunology, 2022)
Hyperammonemia plays a main role in the neurological impairment in cirrhotic patients with hepatic encephalopathy. Rats with chronic hyperammonemia reproduce the motor incoordination of patients with minimal hepatic encephalopathy, which is due to enhanced GABAergic neurotransmission in cerebellum as a consequence of neuroinflammation. Extracellular vesicles (EVs) could play a key role in the transmission of peripheral alterations to the brain to induce neuroinflammation and neurological impairment in hyperammonemia and hepatic encephalopathy, but the underlying mechanisms remain unclear. EVs from plasma of hyperammonemic rats (HA-EVs) injected to normal rats induce neuroinflammation and motor incoordination, but the underlying mechanisms remain unclear. The aim of this work was to advance in the understanding of these mechanisms. To do this we used an ex vivo system. Cerebellar slices from normal rats were treated ex vivo with HA-EVs. The aims were: 1) assess if HA-EVs induce microglia and astrocytes activation and neuroinflammation in cerebellar slices of normal rats; 2) assess if this is associated with activation of the TNFR1-NF-kB-glutaminase-GAT3 pathway; 3) assess if the TNFR1-CCL2-BDNF-TrkB pathway is activated by HA-EVs; 4) assess if the increased TNFα levels in HA-EVs are responsible for the above effects and if they are prevented by blocking the action of TNFα. Ex vivo treatment of cerebellar slices from control rats with extracellular vesicles from hyperammonemic rats induce glial activation, neuroinflammation and enhance GABAergic neurotransmission, reproducing the effects induced by hyperammonemia in vivo. Moreover, we identify in detail key underlying mechanisms. HA-EVs induces the activation of both the TNFR1-CCL2-BDNF-TrkB-KCC2 pathway and the TNFR1-NF-kB-glutaminase-GAT3 pathway. Activation of these pathways enhances GABAergic neurotransmission in cerebellum, which is responsible for the induction of motor incoordination by HA-EVs. The data also show that the increased levels of TNFα in HA-EVs are responsible for the above effects and that the activation of both pathways is prevented by blocking the action of TNFα. This opens new therapeutic options to improve motor incoordination in hyperammonemia and also in cirrhotic patients with hepatic encephalopathy and likely in other pathologies in which altered cargo of extracellular vesicles contribute to the propagation of the pathology.